Performance of Technical Trading Systems in the Yen/Dollar Market - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2007)
The study investigates the profitability of 1,024 moving average and momentum models and their components in the yen/dollar market. It turns out that all models would have been profitable between 1976 and 1999. The pattern of profitability is as follows: the models produce more single losses than single profits, however, the size of the single profits is on average much higher than the size of single losses. Hence, the profitability of technical currency trading is exclusively due to the exploitation of persistent exchange rate trends. These results hold also when technical trading is examined over subperiods. The models which perform best over the most recent subperiod are in most cases significantly profitable also ex ante. However, the profitability of technical currency trading based on daily data has declined since the late 1980s and has disappeared over the out-of-sample period between 2000 and 2004.
Keywords: 330; Performance of Technical Trading Systems in the Yen/Dollar Market Exchange rate; Technical trading; Speculation; Währungsspekulation; US-Dollar; Devisenmarkt; USA; Japan; Finanzanalyse